Dilemmas in the compassionate supply of investigational cancer drugs. Issue 9 (September 2014) - Lewis, J. R. R.; Lipworth, W.; Kerridge, I.; Doran, E.
Abstract In Australia, patients who want to access medicines that are not yet approved have only two options: to enrol in a clinical trial if they are eligible, or obtain their medicine through 'compassionate supply', which is provided at the discretion of the manufacturer. In this article, we explore ethical issues associated with the provision of oncology medicines that are still in development, either prior to regulatory approval or government reimbursement.